Kampo Medicine Treatment for Advanced Pancreatic Cancer: A Case Series - Shimizu, Masayuki; Takayama, Shin; Kikuchi, Akiko; Arita, Ryutaro; Ono, Rie; Ishizawa, Kota; Ishii, Tadashi (Frontiers in Nutrition, 2021)
Aims: The present report aims to investigate the use of Kampo medicine for advanced pancreatic cancer patients in order to prolong survival. Methods: We retrospectively reviewed medical records of patients with pancreatic cancer who presented to our Shimizu Clinic from 2000 to 2020. Patients who survived at least twice as long as the initial prognostic estimate were selected and their treatment was reviewed. The Kampo formula and crude drugs were selected according to the Kampo diagnosis and treatment strategy, which included qi and blood supplementation; qi, blood and water smoothing; and inflammation (termed “heat”) and cancer suppression. Results: Ten patients aged 45–80 years (six males and four females) with stage IV advanced cancer were selected. All patients received hozai, which is a tonic formula, of juzentaihoto (JTT) or hochuekkito (HET) decoction. Anti-cancer crude drugs were included in the decoctions of nine patients. At the first visit, the estimated life expectancy for all patients was no more than 1 year; however, treatment with Western and Kampo medicine led to a relatively long survival period of over 2 years. Three patients were still living at the time of this writing, more than 2, 6, and 14 years after treatment initiation. Conclusion: Our results suggest that Kampo medicine may be useful for disease control and supportive care for patients with advanced pancreatic cancer.